The Practices of Advanced Countries in the Legal Regulation of Intellectual Property Objects Created by Artificial Intelligence - Magauiya, Abay; Omarova, Aiman; Kasenova, Aigul; Akhmetov, Zhasulan; Akhmadi, Marat (Law, State and Telecommunications Review, 2023)
[Purpose] The purpose of this study is to outline the general features of legal regulation in advanced countries of artificial intelligence in the field of intellectual property law, namely in the context of legal regulation of intellectual property rights created by such artificial intelligence. [Methodology/Approach/Design] During the conducted research, the leading method is the comparative legal method. However, apart from it, an array of philosophical, general scientific, and special scientific methods has been used. [Findings] The main results obtained are the analysis of the provisions of regulations governing the specific features of intellectual property rights created by artificial intelligence in advanced countries of the world, such as the United States of America, Great Britain (England, Scotland, Wales, Ireland), the countries of the European Union, etc. [Practical Implications] Practical recommendations are provided for improving the national (Kazakh) legislation in the context of legal regulation of this issue.